Burkitt and Burkitt-like lymphoma/leukaemia at Groote Schuur Hospital from 2005 to 2014: a retrospective review - Koller, Anna J (Division of Haematology, 2022)
Introduction: South Africa has the highest global burden of human immunodeficiency virus (HIV). The HIV seropositive population is at increased risk of developing non-Hodgkin lymphoma, particularly high grade aggressive subtypes such as Burkitt- and Burkittlike lymphoma (also known as B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma). Methods: Ten year retrospective review of clinico-pathological features and survival of adults with newly diagnosed Burkitt- and Burkitt-like lymphoma at a tertiary hospital in South Africa. Results: Burkitt lymphoma (BL) (n=109) was more frequent than Burkitt-like lymphoma (BLL) (n=41) and at presentation there were no significant differences in HIV prevalence (86% vs 78%); median CD4 count (213 vs 207 cells/Î¼L); bone marrow involvement (49% vs 34%), leukaemic dissemination (37% vs 27%) and most frequent site of diagnosis (abdomen/pelvis; 26% vs 29%), respectively. There were significant differences in median age (34 vs 41 years, p=0.0319), median lactate dehydrogenase levels (2052 vs 869 U/l, p=0.0011) and cerebrospinal fluid involvement (12% vs 0%, p=0.046). 43% of patients with an available HIV viral load result showed virological supression defined as lower than detectable limit (LDL) with the median value also being LDL. The patients that received high dose chemotherapy including high dose methotrexate (112/150; 75%) showed a one-year survival of 62% with no significant difference between Burkitt and Burkitt-like lymphoma (66 months versus 51 months, respectively; p=0.267). Patients with leukaemic presentation showed a significantly lower mean survival of 24 months compared to those without (72 months; p< 0.001). The 2 year survival for the whole group, regardless of type of treatment received, was 40% (95% CI, 32-48%) with a median survival of 7.5 months. Conclusion: This is the largest cohort of Burkitt- and Burkitt-like lymphoma patients described in South Africa. There was a high HIV prevalence. The majority received intensive chemotherapy and survival was comparable to certain well-resourced countries. Leukaemic presentation was frequent and associated with less favourable survival.